MENJADIKAN LEGENDA PUTRI PINANG MASAK SEBAGAI IDENTITAS DESTINASI WISATA - SUSILASTRI, DIAN DIAN (Logat: Jurnal Bahasa Indonesia dan Pembelajaran, 2019)
The world of folklore in South Sumatra is rich with princess as female heroes (heroine). Most of them become mighty not by physical strength, but precisely by their gentleness as women. The people of South Sumatra can be proud of their presence, as evidenced by the perpetuation of their name for tourism destinations in the region as regional identity. These princesses, for example Putri Pinang Masak, who is famous for her beauty oaths in the tombs of Senuro Village, Lake/Teluk Gelam, which is told from Putri Gelam, or the story of Putri Buwok Handak, who is famous for her curses and her determination in Kayuagung region, and Putri Dayang Merindu who is cursed by Si Pahit Lidah in the Gua Putri, Baturaja. However, can the tourism destination represent the character of the story that becomes a collective memory of the community owner?             This paper will discuss one of the legends of South Sumatra with princess figure (heroine) as the identity of stories related to tourism destinations. This discussion will focus on the facts of the story of the legend of the princess to show the character of the story as an identity for the development of tourism destinations. Story facts will be analyzed using the text structure analysis method. The design of developing cultural tourism destination is analyzed using the SWOT (Strength, Weakness, Opportunity, and Threats) analysis method to see the possibility of forming the destination character in accordance with the identity of the story. The identity of the story influences the factors of amenities, facilities and infrastructure, connectivity, etc. that would become assets in the cultural tourism attraction. Keywords: legend, cultural potency, tourism destination